A mitochondria-targeting ratiometric fluorescent probe for the detection of hypochlorite based on the FRET strategy. Issue 87 (5th December 2017) - Shen, Shi-Li; Zhang, Xiao-Fan; Ge, Yan-Qing; Zhu, Yan; Cao, Xiao-Qun
Abstract : A novel mitochondria-targeting ratiometric probe (IRP ) for − OCl based on an imidazo[1, 5- a ]pyridine-rhodamine FRET platform was developed. Abstract : In this study, a ratiometric fluorescent probe (IRP ) for − OCl was designed based on the fluorescence resonance energy transfer (FRET) platform. The probe was fabricated by integrating an imidazo[1, 5- a ]pyridine moiety (donor) with a rhodamine moiety (acceptor). We evaluated its properties for recognizing − OCl and the results implied thatIRP possessed high selectivity, a real-time detection possibility and brilliant photostability. The fluorescence intensity ratios ( I 575 / I 467 ) ofIRP displayed desirable − OCl-dependent performance and responded linearly to − OCl in the concentration range of 0.5–3.5 μM. Also, IRP was applied to image endogenous − OCl with a mitochondria-targeting ability, due to the introduction of the quaternized pyridine moiety. Therefore, IRP may be used for further mitochondrial − OCl-related studies.